New network data envelopment analysis approaches: an application in measuring sustainable operation of combined cycle power plants - Faramarzi, Gholam Reza; Khodakarami, Mohsen; Shabani, Amir; Farzipoor Saen, Reza; Azad, Fatemeh (Journal of cleaner production, 2015)
Nowadays, organizations deal with numerous economic, environmental, and social problems. To have sustainable operations, they have begun to incorporate environmental and social concerns into conventional economic objectives. A combined cycle power plant (CCPP) is a good instance of an open system with multistage processes and interconnected activities. Efficiency evaluation of CCPPs is a complex task since there exist a variety of inputs (outputs) which enter into any stages of network. Additionally, there might be intermediate products which are consumed by the same power plants. We call such factors “loop” intermediate measures. To measure efficiency of CCPPs, network data envelopment analysis (NDEA) is used. This paper proposes new NDEA models to evaluate efficiency of CCPPs. The proposed models calculate the efficiency of power plants and their sub-sectors under both CRS (constant returns to scale) and VRS (variable returns to scale) assumptions. This paper provides a comprehensive analysis for returns to scale. We apply the new NDEA models to measure relative efficiency of CCPPs. •This paper provides a comprehensive analysis on returns to scale for DMUs with network structures.•The proposed models are run only one time in order to obtain efficiency of DMUs and their stages.•In our proposed models, weights of stages are unknown and their optimal values are determined.•A wide review of the most recent works on estimation of efficiency and sustainability of power plants has been done.